2011
DOI: 10.1002/cpp.684
|View full text |Cite
|
Sign up to set email alerts
|

Dialectic behavioural therapy has an impact on self‐concept clarity and facets of self‐esteem in women with borderline personality disorder

Abstract: Identity disturbance and an unstable sense of self are core criteria of borderline personality disorder (BPD) and significantly contribute to the suffering of the patient. These impairments are hypothesized to be reflected in low self-esteem and low self-concept clarity. The objective of this study was to evaluate the impact of an inpatient dialectic behavioral therapy (DBT) programme on self-esteem and self-concept clarity. Forty women with BPD were included in the study. Twenty patients were treated with DBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 44 publications
6
30
0
1
Order By: Relevance
“…Moreover, BPD patients have self-concepts that contain a higher proportion of negative attributes than both control groups. This finding is consistent with several studies providing evidence that patients with BPD tend to generate extremely negative evaluations of themselves and others (Arntz & ten Haaf, 2012;Barnow et al, 2009;Klein et al, 2001;Roepke et al, 2011;Rüsch et al, 2007). Concluding from our results, BPD patients rate the majority of their self-aspects as being mostly negative, while few self-aspects are rated as being mostly positive.…”
Section: Measuresupporting
confidence: 95%
See 3 more Smart Citations
“…Moreover, BPD patients have self-concepts that contain a higher proportion of negative attributes than both control groups. This finding is consistent with several studies providing evidence that patients with BPD tend to generate extremely negative evaluations of themselves and others (Arntz & ten Haaf, 2012;Barnow et al, 2009;Klein et al, 2001;Roepke et al, 2011;Rüsch et al, 2007). Concluding from our results, BPD patients rate the majority of their self-aspects as being mostly negative, while few self-aspects are rated as being mostly positive.…”
Section: Measuresupporting
confidence: 95%
“…However, Sieswerda, Arntz, and Wolfis (2005) demonstrated that patients with BPD tended to produce extremely negative, but not split or dichotomous evaluations of themselves on 20 trait visual analogue scales. Consistent with this result, several studies have found that BPD patients possess a more negative selfconcept than non-clinical individuals (Klein, Wonderlich, & Crosby, 2001;Roepke et al, 2011;Rüsch et al, 2007).…”
Section: Self-concept Disturbances In Bpdsupporting
confidence: 75%
See 2 more Smart Citations
“…Those results are aligned with previous ones from other studies that pointed out an significant enhancement in self-concept clarity of the patients that completed the treatment (DBT) compared with those on the waiting list, especially in what concerns to some facets of the self-concept like self-esteem self-regard, social skills and social confidence (Roepke, 2011).…”
Section: Discussionsupporting
confidence: 89%